Sistem Informasi E-Voting Berbasis Web Menggunakan Metode RSA dan Base64 - Cut Lika Mestika Sandy; Reyhan Achmad Rizal; Fadlisyah Fadlisyah (Universitas Muhammadiyah Riau, 2023)
The current problem being faced by Gampong Cot Girek Kandang North Aceh Village is that the selection of Keuchiek is still done manually. Manual selection has many obstacles, one of which is being vulnerable to fraud in voting results because the results cannot be displayed in real-time. Based on these problems, this research will propose an online voting system with web-based e-voting. The web-based e-voting system in this study was created using the RSA and Base64 cryptographic methods to secure voting results data. The results of the study show that a web-based e-voting system using RSA and Base64 is very good for use in the election of Keuchiek besides saving costs because it does not require too many officers and can increase public interest in conducting elections.